Perancangan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di UD. X - Wendyanto William; Kriswanto Widiawan (Jurnal Titra, 2021)
The purpose of this Final Task is to design OHSMS based on Government Regulation number 50 of 2012 which is still within the company’s capabilities. OHSMS design method consists of several stages, namely initial observation, design of initial audit materials, interviews with the company to know capability limits, initial audit, initial recapitulation, OHSMS policy setting, designing OHSMS and design validation. The initial audit results showed the fullfilment of OHSMS criterias by the company was 0 out of 122 criterias set (0%). With the new OHSMS design, the company must meet a minimum of 74 out of 122 criterias set (60%).If it fails, then the design must be reworked. The final audit results showed the company has potential to meet 119 out of 122 criterias set (97.6%). With that being said, the company has fulfilled the requierement needed.